2014
DOI: 10.1073/pnas.1418996111
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3.3 and cancer: A potential reader connection

Abstract: The building block of chromatin is nucleosome, which consists of 146 base pairs of DNA wrapped around a histone octamer composed of two copies of histone H2A, H2B, H3, and H4. Significantly, the somatic missense mutations of the histone H3 variant, H3.3, are associated with childhood and young-adult tumors, such as pediatric high-grade astrocytomas, as well as chondroblastoma and giantcell tumors of the bone. The mechanisms by which these histone mutations cause cancer are by and large unclear. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Although the enzymology of KDM5C as a histone H3K4me3 demethylase is well understood (Lan et al, 2008; Lan and Shi, 2015; Mosammaparast and Shi, 2010), an important question that remains unanswered is how it is recruited to its target regions. We next asked whether RACK7 might play a recruiting role for KDM5C to chromatin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the enzymology of KDM5C as a histone H3K4me3 demethylase is well understood (Lan et al, 2008; Lan and Shi, 2015; Mosammaparast and Shi, 2010), an important question that remains unanswered is how it is recruited to its target regions. We next asked whether RACK7 might play a recruiting role for KDM5C to chromatin.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, enzymes that are involved in modifying the chromatin landscapes of enhancers, such as the histone methyltransferases MLL2, MLL3, MLL4, the H3K4me2/3-specific demethylase KDM5C, the acetyltransferases CBP/p300, as well as the histone H3 variant, H3.3, have been found to be frequently mutated in various cancers (Blair et al, 2011; Ford and Dingwall, 2015; Lan and Shi, 2015; Rasmussen and Staller, 2014; Wang et al, 2013). Consistently, recent cancer genome sequence efforts have also identified genetic mutations of enhancers and super-enhancers, which regulate the expression of oncogenes and tumor suppressors (Fredriksson et al, 2014; Melton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin modifiers are frequently mutated in medulloblastomas 71 and in small cell lung cancer 72 . Similarly, pediatric glioblastomas 73 and some other brain tumors (e.g., diffuse intrinsic pontine glioma and high-grade astrocytoma) are characterized by recurrent driver mutations in H3F3A encoding replication-independent histone variant H3.3 (reviewed in 74 ). The same gene is mutated in chondroblastoma, chondrosarcoma, and osteosarcoma 74 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, pediatric glioblastomas 73 and some other brain tumors (e.g., diffuse intrinsic pontine glioma and high-grade astrocytoma) are characterized by recurrent driver mutations in H3F3A encoding replication-independent histone variant H3.3 (reviewed in 74 ). The same gene is mutated in chondroblastoma, chondrosarcoma, and osteosarcoma 74 . It has been shown that mutations in H3.3 may alter either local or global histone methylation patterns (reviewed in 74 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation